2023
DOI: 10.3390/pharmaceutics15030863
|View full text |Cite
|
Sign up to set email alerts
|

Naringin: Nanotechnological Strategies for Potential Pharmaceutical Applications

Abstract: Polyphenols comprise a number of natural substances, such as flavonoids, that show interesting biological effects. Among these substances is naringin, a naturally occurring flavanone glycoside found in citrus fruits and Chinese medicinal herbs. Several studies have shown that naringin has numerous biological properties, including cardioprotective, cholesterol-lowering, anti-Alzheimer’s, nephroprotective, antiageing, antihyperglycemic, antiosteoporotic and gastroprotective, anti-inflammatory, antioxidant, antia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 90 publications
0
9
0
Order By: Relevance
“… Flavanones , especially naringenin and hesperidin, are inserted into TP with an anti-inflammatory purpose. They are used for atopic dermatitis, WD nanoemulsions or nanogels on different polymeric supports, or lipidic nanocarriers [ 186 , 187 , 188 ]. Flavones represented by apigenin, which is a hydrophobic flavone, have been used in several formulations so far for TD, including liposomes, nanocrystal gel formulations, and self-micro-emulsifying delivery systems for anti-inflammatory and breast cancer treatment [ 189 , 190 ].…”
Section: Natural Products From Plants Used In Medical Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“… Flavanones , especially naringenin and hesperidin, are inserted into TP with an anti-inflammatory purpose. They are used for atopic dermatitis, WD nanoemulsions or nanogels on different polymeric supports, or lipidic nanocarriers [ 186 , 187 , 188 ]. Flavones represented by apigenin, which is a hydrophobic flavone, have been used in several formulations so far for TD, including liposomes, nanocrystal gel formulations, and self-micro-emulsifying delivery systems for anti-inflammatory and breast cancer treatment [ 189 , 190 ].…”
Section: Natural Products From Plants Used In Medical Devicesmentioning
confidence: 99%
“…Flavanones , especially naringenin and hesperidin, are inserted into TP with an anti-inflammatory purpose. They are used for atopic dermatitis, WD nanoemulsions or nanogels on different polymeric supports, or lipidic nanocarriers [ 186 , 187 , 188 ].…”
Section: Natural Products From Plants Used In Medical Devicesmentioning
confidence: 99%
“…We previously found that Si-Ni-San, a traditional Chinese medicine formula, was capable of promoting estrogen metabolism in the liver, and naringenin (NAR) has been identified as a potential bioactive compound targeting EST [ 23 ]. However, the poor solubility and bioavailability of NAR limits its efficacy [ 24 ]. In the past decades, nanoparticle-based drug delivery systems have emerged as a powerful tool for cancer therapy, such as photothermal therapy [ 25 ], sonodynamics [ 26 , 27 ], and redox targeting strategies [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Icariin shows promising characteristics in biomedicine and bone/cartilage tissue engineering [10]. Naringin (4 , 5,7-trihydroxy flavanone-7-rhamnoglucoside, Figure 1) is a flavonoid glycoside that is found in the extract of citrus fruits [11] and rhizoma drynariae [12]. Naringin possesses several pharmacological effects, including anti-inflammation, anti-oxidation, anti-cancer, anti-bacteria, liver protection, and bone/cartilage protection [13,14].…”
Section: Introductionmentioning
confidence: 99%